DESTINASI WISATA, SUMBER DAYA MANUSIA PARIWISATA DAN PARIWISATA BERKELANJUTAN - Titing Koerniawati, Francicca (SIWAYANG Journal: Publikasi Ilmiah Bidang Pariwisata, Kebudayaan, dan Antropologi, 2022)
The development of world tourism experienced a surge in tourist arrivals both international and domestic. Developments, the share of the global tourism market and new opportunities to serve the middle class is growing rapidly. The group of potential domestic tourists are expected to ensure that tourism remains a strategic sector in the national development agenda. Indonesia is very much has a very attractive tourist destination, and Bali in particular, of course, strongly felt the impact of the surge in tourist arrivals. Readiness of Tourism Human Resources are needed to support the sustainable tourism program.